Significant correlation between peripheral blood CD34+ cell count in children prior to aphaeresis and CD34+ cell yield following aphaeresis: A single‐center experience. (2nd March 2018) - Rosenfeld‐Keidar, Hila; Eshel, Rinat; Pinhasov, Aviva; Bitan, Menachem; Edelman, Sabina; Broitman, Marcela; Dvir, Rina; Sadot, Efraim; Levin, Dror; Manisterski, Michal; Berger‐Achituv, Sivan; Elhasid, Ronit
Abstract: Numerous adults' studies demonstrated that preaphaeresis CD34+ cells significantly correlate with the number of CD34+ cells collected by the aphaeresis procedure. Equivalent studies in children are scarce. We studied retrospectively 92 aphaeresis procedures performed following chemotherapy (44) or in steady state (48) in 60 pediatric patients (40 males, 20 females), median age of 7.5 years. Aphaeresis procedures were performed using a SPECTRA Optica (TERUMOBCT) continuous flow cell separator. CD34+ cell concentrations were assessed using flow cytometry. A highly significant correlation between peripheral CD34 cell count on the day of aphaeresis and CD34 cell yield per kg ( R 2  = .824, P  <   .0001) was demonstrated. A higher preaphaeresis CD34 cell count was demonstrated in patients with higher preaphaeresis white blood cell count, in patients with brain tumors, and in patients who received chemotherapy as part of their mobilization protocol. A threshold number of 20 peripheral CD34+ cell/μL was found to predict harvesting of 3 × 10 6 stem cells/kg, and 30 peripheral CD34+ cell/μL for harvesting of 5 × 10 6 stem cells/kg. This significant correlation between peripheral CD34 cell count and CD34 cell yield, and the threshold number of peripheral CD34 found to predict adequate harvesting can be useful in planning the optimal time for aphaeresis in children.